A catequese nos primórdios da cidade de São Paulo Piratininga revisitado por ocasião dos 450 anos de sua fundação - Suess, Paulo (Revista Eclesiástica Brasileira, 2004)
A história da cidade de São Paulo e do Brasil é uma história de desaparecimentos e esquecimentos, de resistências e lutas pela sobrevivência física e cultural, de transformações e adaptações. Arar a memória dos destinatários e dos agentes da primeira evangelização, por ocasião dos 450 anos da “conversão do Brasil”, é uma tarefa instigante, sobretudo no contexto histórico de hoje, onde a pergunta sobre a possibilidade de um outro mundo é ao mesmo tempo uma pergunta sobre a relevância da evangelização. A comemoração da fundação da “Casa de Piratininga”, um pobre colégio que se tornou megalópole, tem a tarefa de religar o conhecimento histórico ao reconhecimento contemporâneo do outro. O Autor, missiólogo e historiador, por muitos anos ligado à causa indígena no país e no continente latino-americano, conduz o leitor pela cristandade do Brasil e pela diversidade étnica da Província de São Vicente. Dois eixos da evangelização ganham destaque: a questão da comunicação num contexto lingüístico plural e a questão da violência e da força diante da proposta evangélica de gratuidade e paz. Abstract: The history of the city of São Paulo and Brazilian history, in general, are full of disappearances and omissions, of resistance and struggles for physical and cultural survival, of transformations and adaptations. On the occasion of the 450th anniversary of the “conversion of Brazil”, to trace the memories of both addressees and agents of the first evangelization is a stimulating task, particularly in today’s historical context, where the question about the possibility of another world is, at the same time, a question about the relevance of evangelization. The celebration of the foundation of the “Casa de Piratininga”, an ordinary school that became a megalopolis, seeks to reconnect historical knowledge to the contemporary recognition of the Other. The Author – a missiologist and historian that, for many years, has been connected with the Indian cause in this country and in the Latin-American continent – guides the reader through the Christendom in Brazil and through the ethnical diversity in the Province of São Vicente. He focuses, in particular, on two axles of the evangelization: the issue of communication in a plural linguistic context and the issue of violence and coercion in the face of the evangelical proposal of graciousness and peace.